Views of Tax Agents on The Malaysian Tax System and Compliance Burden: Qualitative Analysis - Sapiei, Noor Sharoja; Abdullah, Mazni; Ismail, Kamisah; Zainuddin, Suria (Asian Journal of Accounting Perspectives, 2011)
This study focuses on the compliance burden of Malaysian corporations from the perspective of tax agents. Two main areas are investigated, namely, suggestions for reducing the tax compliance burden of companies and improving the Malaysian tax system. Based on the qualitative analysis, the following measures are laid out from the perspective of lowering the compliance burden: (i) improve the accountability and transparency in tax administration matters, (ii) simplification of tax incentive requirements, and (iii) convergence of tax law with accounting standards in order to reduce discrepancy and tax adjustments. This study benefits the tax literature and the Malaysian tax practice by providing reliable qualitative research findings for establishing guidelines and policies pertaining to the compliance burden of corporate taxpayers.